Interpretation of the Signs in the Tradition of Ma Baca-Baca Among the Muslim Society of Bugis Bone - Agustina Riska Eka Saputri Riska; Dadan Rusmana (HUMAYA Jurnal Hukum Humaniora Masyarakat dan Budaya, 2021)
This research aims to explain the signs contained in the tradition of ma'baca-baca among the Muslim society of Bugis Bone and the meaning of the signs. The research problems consist of: 1) What are the signs found in the tradition of ma'baca-baca among the Muslim society of Bugis Bone; 2) What is the meaning of the signs that exist in the tradition of ma'baca-baca among the Muslim society of Bugis Bone. To analyze these problems, the theory used is the semiotic theory of Charless Sanders Peirce, which proposes a triangle theory of meaning, linking three aspects which are the main elements, namely representamen (sign), object, and interpretant. And assisted by Bronislaw Malinowski's theory of cultural functionalism. While the research method used is a qualitative descriptive method, namely the techniques of observation, interviews, and documentation. This study resulted in the following conclusions; 1) There are 5 verbal signs and there are 18 nonverbal signs in the tradition of ma’baca-baca among Muslim society of Bugis Bone, 2) All signs contained in the tradition of ma'baca-baca have their own meanings that are interpreted and believed by the local society.